Simplified modeling and optimization of silicon modulators based on free-carrier plasma dispersion effect - Pérez-Galacho, Diego; Marris-Morini, Delphine; Stoffer, R.; Cassan, E.; Baudot, C.; Korthorst, T.; Boeuf, F.; Vivien, L. (Optical Publishing Group, 2016)
n this paper, a simplified model of silicon phase modulators is presented that enables favorable accuracy together with a substantial reduction in computational effort and without the requirement of semiconductor TCAD device simulation software. This permits fast optimization of the different parameters of a modulator. The model was successfully implemented in Phoenix Optodesigner optical software allowing the optimization of silicon phase shifters for different applications. Moreover, this model presents a great potential for the simulation of modulators based on PN interdigitated junctions, which normally require complex and time consuming 3D simulations. Simulation time was reduced by a factor of 6 for the lateral PN junction based modulator, and two orders of magnitude reduction was obtained for interdigitated PN junctions based modulators.
Keywords: Comunicaciones ópticas; Modulators; Optoelectronics; Integrated optics; Integrated opticas devices